Place Identity in Defining Urban Space of Border Rivers in Historical City Centres (Journal of Engineering, 2014)
In the city, building space could transform to be as place, because architecture does not include only traditional values such as housing, human protection, stability, etc, but could carry other dimensions beyond the housing or building occupancy or develop urban design. Rivers had vision in motion as a way to show dynamic processes in its flowing slowly, which are simply measured in time and the life of citizens. The research consider the river path in traditional cities as Alley connecting the spaces of the city ... old Baghdad was characterized by this property and it is look like Venice in the past, while traditional European cities were able to preserve this property till now, and capable to take transformation of the city with development projects inside it. These cities was distinguished by development of river edge as creating place along the river corridor and try to attract peoples who lived in, protect the natural environment along the river, as well as reflect the characteristics of the city along of the elevation of the river, and conserve the river banks as alley connected between urban spaces. Baghdad which penetrates by Tigris River has maintained this feature until the middle of twentieth century. So now, the research can see the absence of specialized local studies, including The comprehensive development plan of the Baghdad city 2030 to study and Re design the spaces and places along river edge, this led to emerge research problem, in the absence of specific knowledge about identity of river space characteristics for identification of urban space in place of the Tigris River in downtown of Baghdad historical city center, in the urban development plans since the mid-twentieth century until now, and study design factors that contributed with disintegration of the space syntax relations in river elevation. Turning to the experience of historical European cities and how to deal with urban space to the edge of the river and created the identity of the place, especially the interface development experience the (Seine river in Paris, Thames River in London, Tiber River in Rome, Danube River in Vienna & Budapest, Vltava river in Prague) and study urban style in dealing with the river edge, in order to reach the elements which define the identity of each city. In order to reach the aim of research in redefining the identity of places for urban spaces overlooking to integrate the banks of Tigris River in the historical city centre of Baghdad, and the methods of linking the development of river front with the comprehensive development plan of the Baghdad city 2030.